A critical analysis of the international legal framework regulating the microbiological classification of bivalve shellfish production areas - Robson Ventura de Souza; Carlos Campos; Luis Hamilton Pospissil Garbossa; Luiz Fernando de Novaes Vianna; Argeu Vanz; Guilherme Sabino Rupp; Walter Seiffert (Reviews in Aquaculture, 2018)
This study presents a review of the microbiological standards and associated monitoring practices for classification of commercial shellfish production areas in force in Brazil, European Union and United States of America. The classification systems are not immediately comparable principally because some regulations are based on the monitoring of water and others of shellfish flesh. To create a common baseline to compare these regulations, regression models were developed based on monitoring data and used to correlate levels of faecal indicator bacteria in water and in shellfish. The classification system used in the European Union was found to provide the highest level of shellfish safety for classification categories that do not require post‐harvest treatments prior to marketing, while the United States system provides higher level of shellfish safety for classification categories that require these treatments. The Brazilian legislation prescribes depuration as the post‐harvest treatment for shellfish with much higher levels of coliforms than the United States and European Union systems. Evidence was found that the microbiological limits for sea water set out in the Brazilian Resolution 357 – CONAMA are more stringent than the regulations used in the European Union and United States. The results also suggest that the Brazilian Shellfish Sanitation Programme and the European Union legislation are the least stringent concerning maximum faecal contamination tolerated. This assessment provides information on margins of safety for shellfish products traded internationally.